(untitled) (Research, Society and Development, 2020)
The work had as objective to know the density and the composition of forest species of the litter bank of the litter and the soil in a recovery area, in Guarapuava, PR. Fifty - five plots (100m² each) were installed, the forest census was carried out, and three basal areas were defined: basal area - T1, basal area - T2 and basal area - T3. Were 25 soil and 25 litter samples were collected at the end of each season and taken to the greenhouse for a period of 8 months for seedling emergence, with monthly assessment, identification and counting. 17.303 individuals belonging to 80 species and 42 families were identified. Of these, 89.6% are herbaceous, belonging to 62 species and distributed in 31 families and 10.4%, are forest / shrub species, belonging to 18 species and 14 families. The most representative forest / shrub species were M. scabrella and Baccharis sp. with 492 and 1,051 individuals, respectively. The winter season had the highest number of seedlings, followed by summer and autumn, differing statistically from spring. In the inner part of the forest, a greater number of species, individuals and forest species were sampled than in relation to the edge, a trend observed in seasons and also in relation to soil samples when compared to litter samples. The similarity between the seed bank and the regeneration was high (0.48) and between the seed bank and the arboreal stratum was lower (0.28). It is suggested that the area without intervention has been able to develop and establish new species.